Effectiveness of education and training programmes to help clinicians assess and classify perineal tears: a systematic review - Caroline Homer; Alyce N Wilson; Alexander John Eggleston; Annabel Richards; Grace Simpson; Joshua Peter Vogel; Moira Philip (BMJ Open, 2025)
Objective For every 100 women having a vaginal birth, approximately four will experience a severe (third-degree or fourth-degree) perineal tear. Severe perineal tears are associated with significant short-term and long-term consequences if not recognised and repaired. There are global efforts to reduce incidence of severe perineal tears including initiatives to strengthen education and training of clinicians in perineal anatomy and perineal tear assessment and classification. This systematic review aimed to describe and evaluate the effectiveness of these initiatives.Design Systematic review, reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.Data sources Medline (Ovid), CINAHL Complete (EBSCO), MIDIRS and EMBASE (Ovid) were searched through 15 February 2024.Eligibility criteria Studies reporting simple or complex interventions aimed at improving the skills and knowledge of clinicians in perineal anatomy and/or the clinical assessment and classification of perineal tears were eligible.Data extraction and synthesis Two reviewers independently screened studies for eligibility and appraised the quality of individual studies using the Cochrane Risk of Bias (RoB) 2.0 tool or Risk of Bias in Non-Randomised Studies of Interventions (ROBINS-I) tool.Results In total, 7645 citations were screened and 39 studies included. We identified nine unique interventions including training programmes, short workshops and senior obstetrician supervision. Many studies were from high-income countries, in primary care settings and at high risk of bias.Conclusions Effective education included practical components, such as hands-on skills and training in perineal anatomy, assessment and classification, rather than senior supervision alone. Ongoing review of practice appears to be crucial for maintaining knowledge and skills. Future research should focus on interventions tailored to limited-resource settings, and the optimal length and intensity of training programmes to assess and classify perineal tears.PROSPERO registration number CRD42020185431.